ФУНКЦИОНАЛЬНАЯ АКТИВНОСТЬ ТРОМБОЦИТОВ У БОЛЬНЫХ АСТРАХАНСКОЙ РИККЕТСИОЗНОЙ ЛИХОРАДКОЙ С СОПУТСТВУЮЩЕЙ ГИПЕРТОНИЧЕСКОЙ БОЛЕЗНЬЮ - Н. Р. Бедлинская; Х. М. Галимзянов; Е. Н. Лазарева (Архивъ внутренней медицины, 2012)
The analysis of functional activity of platelets at patients with middle severity of illness of Astrakhan rickettsial fever with accompanying hypertensive illness depending on age was carried out. At patients were more senior 50 years of change of activity platelets in an illness heat were expressed more brightly and weren’t restored during the period of reconvalescence.